A quinoprotein dehydrogenase from Pelagibacterium halotolerans ANSP101 oxidizes deoxynivalenol to 3-keto-deoxynivalenol. (June 2022) - Qin, Xiaojuan; Zhang, Jing; Liu, Yanrong; Guo, Yongpeng; Tang, Yu; Zhang, Qiongqiong; Ma, Qiugang; Ji, Cheng; Zhao, Lihong
Abstract: Deoxynivalenol (DON), a notorious mycotoxin commonly present in cereal grains, poses severe health risks to human and livestock. A quinoprotein from Pelagibacterium halotolerans ANSP101, named deoxynivalenol dehydrogenase (DDH), was identified by comparative genome analysis of P. halotolerans ANSP101, Devosia mutan 17-2-E−8 and Devosia strain IFO13580. DDH was responsible for oxidation of DON into 3-keto-DON with hydrogen acceptor phenazine methosulfate (PMS) or dichlorophenolindophenol (DCPIP). DDH had two catalytic amino acid residues (Ser478, Glu480), and 57.55% sequence identity with quinoprotein dehydrogenases DepA from Devosia sp. 17-2-E−8 and QDDH from Devosia sp. D6-9 by sequence alignment. The Met516 of DDH was changed to Glu516 by site-specific mutagenesis, and the new mutant was designated as TDDH. The mutant TDDH possessing catalytic triplet SEE (Ser478, Glu480, Glu516) could degrade DON to 3-keto-DON with pyrroloquinoline quinone (PQQ) as hydrogen acceptor besides PMS and DCPIP. Importantly, the mutant TDDH exhibited stronger degradation ability for DON in the presence of the same hydrogen acceptor compared with wild DDH. The mutant TDDH had an effect on degrading DON with PQQ at a wide range of pH (6.0–11.0) and temperatures (20–45 °C). The results provide potential use of TDDH as a detoxification agent to mitigate DON hazard on human and animals applied in food and feed. Highlights: Deoxynivalenol dehydrogenase (DDH) is identified by comparative genome analysis. DDH is responsible for oxidation of DON into 3-keto-DON with hydrogen acceptor. The mutant TDDH (Met516 to Glu516) had catalytic triplet and could degrade DON. TDDH possesses higher degrading ability for DON compared with wild DDH. TDDH functions at a wide range of pH and temperatures on degrading DON with PQQ.